Fédéralisme, asymétrie et interdépendance : aux origines de l’action internationale des composantes de l’État fédéral - Dehousse, Renaud (Études internationales, 1989)
This article deals with a problem relatively neglected by studies devoted to the foreign relations of federated states, namely the reasons that impel the member Itates of some federations to develop foreign affairs policy independently of each other. Several types of factors are taken into consideration. It appears that the growing interdependence of industrialized countries leads to both an increase and a diversification of international contacts between public authorities, thus undermining he traditional monopoly held by external affairs departments. This phenomenon, however, does not arise to the same degree in all federations, suggesting that internal factors may equally play a major role. The composite character and above all the asymmetry of some federations have, clearly enough, centrifugal effects. But the influence of institutional variables must not be neglected: the combination of a particularly pronounced asymmetry together with weaknesses n the representation accorded at the national level to different regions making up the federation probably explain the activism shown by Belgium's linguistic communities and some Canadian provinces.